Effects of pavement surface deformations on traffic flow - Aydin, Metin Mutlu; Topal, Ali (Transport, 2019)
Pavement surface deformations have a significant effect on speed profile of vehicles and traffic flow conditions. These deformations limit driving properties and increase vehicle operation and maintenance costs. Additionally, they cause many problems such as accidents, slower movement speeds, capacity loss and severe discomfort states. There are many factors having an effect on road capacities and they vary according to different road and traffic flow conditions. In this study, it is aimed to investigate and develop models to estimate shockwave and bottleneck forming, capacity loss and speed reduction, which occurred on examined road links caused by pavement deformations. For the prediction of road capacity, flow–density (q–k) relationship, bottleneck and shockwave analysis methods were used. In the scope this study, deformed road links were divided into three sections; Section A – before deformation zone, Section B – deformation zone, and Section C – after deformation zone. All three sections were investigated and empirical results were obtained. According to analysis results, it was found that pavement surface deformations have a negative effect on the level of road service capability. Obtained results also showed that there are significant reductions in capacity relatively by up to 44 and 26% would result from surface deformations on deformed lanes and non-deformed adjacent lanes.